Palestine Refugees : Education Resilience Case Report - World Bank (Washington, DC, 2014)
This country report and the data presented herein form part of the development of the resilience research training module, called "Resilience in Education Systems Research" or RES-Research in Palestine. This initial approach was qualitative and focused on the voices of students from UNRWA schools in these three regions. Qualitative data approaches lend themselves to the study of education resilience, as they better uncover the more complex and unobservable human and social factors that cannot be captured through quantitative data collection and analysis alone.